(untitled) - Eikamp, Arthur (Langlois, 2000)
This is the account of the experiences of a farm boy from the western prairie and a girl from the Bronx. These two spent 35 years in Japan. No two societies could be more different This is the story of their struggle to understand, their mistakes, the humorous situations they find themselves in, all against the background of the American occupation and the Korean conflict next door. It contrasts American and Japanese life and tells the story of many courageous Japanese and their response to life situations. It tells of their being ushered in to meet the Emperor and of his kind words of thanks. It is the account of the trip from culture shock to true bi-cultural living.
Keywords: Giáo viên, ngoại ngữ,Teachers, Foreign; Tiểu sử,Biography; Nhật Bản,Japan